The Effectiveness of the Traditional Rangku Alu Game in Improving the Agility of Elementary School Students - Noova Brilyan Diptanugraha Noova; Khamim Hariyadi; Muhammad Soleh Fudin; Abubakar Isyaku Ismail (CV Media Inti Teknologi, 2025)
Background of Study: The low agility of students in Physical Education, Sports, and Health (PJOK) learning is often caused by conventional methods that lack variation and do not optimize traditional games. Rangku Alu, a rhythmic movement game involving agility, coordination, and quick direction changes, aligns with PJOK learning goals and helps preserve local culture. Aims and Scope of Paper: This study aims to determine the effectiveness of the traditional Rangku Alu game in improving the agility of fifth-grade elementary school students and to propose it as an alternative, fun, interactive, and culturally relevant PJOK learning method. Methods: A quantitative experimental approach with a one-group pretest-posttest design was applied to 11 fifth-grade students at SDN 3 Sumberdadi. Agility was measured using the Hexagon Drill Test before and after eight PJOK sessions integrating Rangku Alu. Data were analyzed using the Shapiro-Wilk normality test, Paired Sample t-Test, and N-Gain test. Result: The average pretest time decreased from 14.30 seconds to 11.90 seconds in the posttest. The t-test yielded a significance value of 0.000 (p < 0.05), and the N-Gain average was 65%, indicating moderate effectiveness. Conclusion: The Rangku Alu game significantly improves students’ agility and can serve as an effective, enjoyable, and culturally based alternative in PJOK learning. It also supports cultural preservation in the school environment while promoting active participation and holistic physical development.